High-breathability wear-resistant medical composite fabric and preparation method thereof
By using hydrophobic layer and wear-resistant layer structure in medical composite fabrics, and using materials such as carbon nanotube resin to form an antibacterial structure, the problem of insufficient breathability and antibacterial properties of existing fabrics is solved, and the preparation of high breathable and wear-resistant medical composite fabrics is achieved, which significantly improves the performance and service life of the fabrics.
Patent Information
- Application Number
- CN202411626026.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing medical composite fabrics have poor breathability and antibacterial properties in applications such as protective clothing, and insufficient wear resistance, resulting in waste of resources and increased costs.
A highly breathable and wear-resistant medical composite fabric composed of a hydrophobic layer and a wear-resistant layer is used to make the wear-resistant layer by spinning and meltblowing of materials such as carbon nanotube resin and polybenzaldehyde-based ethylene acrylate. Sodium hydrosulfide is used for hydrothermal rolling to form a polythiophene and pyrrolopyrrole structure to enhance antibacterial properties.
It significantly improves the breathability, wear resistance and antibacterial properties of the fabric, extends the service life, and reduces resource waste and production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a highly breathable and wear-resistant medical composite fabric and a preparation method thereof. Background Art
[0002] Disposable masks, protective masks, protective clothing, and disinfectant wipes play a very important role in the prevention and treatment of infectious diseases. However, due to technical barriers, a large number of materials for the prevention and treatment of infectious diseases have poor quality and breathability. Medical staff are often sweating and even suffering from heat stroke and shock due to the protective clothing they wear, and materials for the prevention and treatment of infectious diseases are easily worn out.
[0003] Medical composite fabrics are widely used in the preparation of disposable masks, protective masks, protective clothing, disinfectant wipes and other materials due to their unique functions, and have played a great role in the prevention and treatment of infectious diseases. However, although medical composite fabrics have the advantages of high shielding and high particle filtration efficiency, they are widely used in the medical field. However, as a protective material, its wear resistance is poor, so technicians add carbon nanotubes to the meltblown cloth for compounding to enhance its wear resistance. However, during use, people found that the air permeability and antibacterial properties of the meltblown cloth after technical improvements were extremely poor, and the reuse rate was low, resulting in waste of resources and a sharp increase in costs.
[0004] The present invention has paid attention to this problem and found that people's daily activities are often carried out under indoor lighting conditions with an illumination of not less than 200lx. Therefore, in order to utilize this light energy to enhance the antibacterial properties of medical composite fabrics, the present invention prepares a highly breathable and wear-resistant medical composite fabric to solve this problem. Summary of the invention
[0005] The object of the present invention is to provide a highly breathable and wear-resistant medical composite fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A highly breathable and wear-resistant medical composite fabric is obtained by laminating a hydrophobic layer and a wear-resistant layer from bottom to top and performing hydrothermal roller pressing using sodium hydrosulfide.
[0007] Furthermore, the wear-resistant layer is prepared by mixing carbon nanotube resin and polybenzaldehyde-based ethylene glycol acrylate through reaction spinning and melt-blowing.
[0008] Furthermore, the carbon nanotube resin is prepared by mixing and reacting amino carbon nanotubes and polyvinyl iodophenyl acetonitrile; the amino carbon nanotubes are prepared by mixing and reacting 1-(4-amino-2-hydroxyphenyl)-2,2-dichloro-ethanone and acidified carbon nanotubes.
[0009] Furthermore, the hydrophobic layer is obtained by spinning and twisting poly(vinylphenylacetic acid butylene glycol) ester.
[0010] Furthermore, a method for preparing a highly breathable and wear-resistant medical composite fabric is provided. The method for preparing the highly breathable and wear-resistant medical composite fabric is as follows: (1) Under argon protection, carbon nanotube resin, polybenzaldehyde-based ethylene glycol acrylate, acetic acid, and deionized water were mixed in a mass ratio of 1:0.7:0.2:0.7-1:0.9:0.4:0.9, and 80% sulfuric acid with a mass fraction of 0.2-0.4 times the mass of the carbon nanotube resin was added at a rate of 40-60 drops / min. The mixture was stirred at 400-600 r / min for 2-4 hours, and then placed in a condensation drum with a rotation speed of 92-96 m / min and a melt-blown die. In a melt-blowing device with a head aperture of 5-7 μm, a die temperature of 221-225°C, and a hot air pressure of 0.21-0.23 MPa, the receiving distance is adjusted to 38-42 cm, the extrusion frequency is adjusted to 1.5-2.5 Hz, and the hot air temperature is adjusted to 245-255°C for melt-blowing, and then the electret voltage is controlled to 38-42 kV, and the electret distance is 2.5-3.5 cm for electret 0.8-1.2 min to obtain a 0.8-1.2 mm thick wear-resistant layer; (2) Under argon protection, 4-ethynylphenylacetic acid and butanediol were mixed at a mass ratio of 1:0.5-1:0.7, concentrated sulfuric acid (0.6-0.8 times the mass of 4-ethynylphenylacetic acid) was added at a rate of 40-60 drops / min, the temperature was raised to 140-150°C, and the mixture was stirred at 600-800 r / min for 2-4 hours. Diisopropyl peroxydicarbonate (0.6-0.8 times the mass of 4-ethynylphenylacetic acid) was added at a rate of 40-60 drops / min, the temperature was lowered to 63-65°C, and the mixture was continued. Stirring for 59-61 minutes to obtain polyethynylphenylacetic acid butylene glycol ester; placing the polyethynylphenylacetic acid butylene glycol ester in a spinning box at 140-160° C., spinning using a screw extruder at a spinning speed of 800-1000 m / min, side-blowing cooling and curing for 25-35 minutes at 10-20° C., a humidity of 60-80% and a wind speed of 0.9-1.3 m / s, co-twisting and weaving to obtain a hydrophobic layer with a thickness of 0.3-0.5 mm; (3) Lay the hydrophobic layer and the wear-resistant layer from bottom to top, immerse them in deionized water 0.7~0.8 times the mass of the hydrophobic layer, roll them 2~3 times at a rolling speed of 123~260m / min, a roller distance of 1.4~2.9mm and a pressure of 0.25~0.35Mpa, add sodium hydrosulfide 0.5~0.7 times the mass of the hydrophobic layer, stir at 600~800r / min at 60~80℃ and 0.3~0.5MPa for 30~40min, add sodium 0.6~0.8 times the mass of the hydrophobic layer, raise the temperature to 183~185℃, and continue stirring for 3~5h , cool to -1~1℃, add triethylamine (0.54~0.56 times the mass of the hydrophobic layer), continue stirring for 51~53h, heat to 24~26℃, add silver-copper catalyst (0.02~0.04 times the mass of the hydrophobic layer), continue stirring for 7~9h, then add 4-methylbenzenesulfonic acid (0.004~0.006 times the mass of the hydrophobic layer) and acetic acid (5~7 times the mass of the hydrophobic layer), heat to 88~92℃, continue stirring for 11~13h, remove, wash with ethanol and deionized water 2~4 times, put into 55~65℃ oven for 6~8h, and obtain highly breathable and wear-resistant medical composite fabric.
[0011] Furthermore, the preparation method of the carbon nanotube resin in step (1) is as follows: under argon protection, polyvinyl iodobenzene acetonitrile and amino carbon nanotubes are mixed in a mass ratio of 1:0.6-1:0.8, ultrasonically oscillated at 38-47 kHz for 25-35 min, and then sodium hydride and copper are added in a mass ratio of 1:0.2-1:0.4, wherein the mass of sodium hydride is 0.4-0.6 times the mass of polyvinyl iodobenzene acetonitrile, heated to 110-120°C, and stirred at 300-500 r / min for 12-13 h at 10-20 Pa to obtain the carbon nanotube resin.
[0012] Furthermore, the preparation method of the polyvinyl iodobenzene acetonitrile is as follows: under argon protection conditions, polyvinyl chloride with a molecular weight of 8000-10000 and 4-iodobenzene acetonitrile are mixed in a mass ratio of 1:1.2-1:1.4, stirred at 300-500 r / min for 20-30 min, and then 0.02-0.06 times the mass of polyvinyl chloride is added with aluminum chloride, cooled to 0-4°C at 4-6°C / min, and stirred at 500-700 r / min for 7-9h to obtain polyvinyl iodobenzene acetonitrile.
[0013] Furthermore, the preparation method of the amino carbon nanotubes in step (1) is as follows: carbon nanotubes and concentrated sulfuric acid are mixed in a mass ratio of 1:210 to 1:230, ultrasonically oscillated at 38 to 47 kHz for 25 to 35 minutes, then concentrated nitric acid with a mass fraction of 68% of 55 to 57 times the mass of the carbon nanotubes is added, stirred at 1200 to 1400 r / min for 9 to 11 minutes, heated to 58 to 62° C., continued stirring for 1.5 to 2.5 hours, added with deionized water with a mass fraction of 98 to 102 times the mass of the carbon nanotubes for dilution, allowed to stand for 3.5 to 4.5 hours, then vacuum filtered with a microporous filter membrane with a pore size of 220 nm, washed with deionized water until the filtrate has a pH of 7, and then washed with anhydrous ethanol. The method comprises the following steps: washing 2 to 4 times, placing the carbon nanotubes in an oven at 55 to 65°C for 40 to 60 minutes, and obtaining acidified carbon nanotubes; adding the acidified carbon nanotubes to ether with a mass of 20 to 30 times the mass of the carbon nanotubes, ultrasonicating at 38 to 47 kHz for 25 to 35 minutes, adding 1-(4-amino-2-hydroxyphenyl)-2,2-dichloro-ethanone with a mass of 0.8 to 1 times the mass of the acidified carbon nanotubes, and adding concentrated sulfuric acid with a mass of 0.6 to 0.8 times the mass of the acidified carbon nanotubes at a rate of 40 to 60 drops / min, heating to 60 to 80°C, continuing stirring for 1 to 3 hours, filtering, washing with anhydrous ethanol and deionized water for 2 to 4 times, respectively, placing the carbon nanotubes in an oven at 55 to 65°C for 40 to 60 minutes, and obtaining amino carbon nanotubes.
[0014] Furthermore, the preparation method of the polybenzaldehyde-based ethylene glycol acrylate in step (1) is as follows: under argon protection, 4-methylphenylacrylic acid and ethylene glycol are mixed in a mass ratio of 1:0.6 to 1:0.8, concentrated sulfuric acid with a mass of 0.6 to 0.8 times that of 4-methylphenylacrylic acid is added dropwise at a rate of 40 to 60 drops / min, the temperature is raised to 70 to 80°C, stirred at 600 to 800 r / min for 2 to 4 hours, and 4-methylphenylacrylic acid is added dropwise at a rate of 40 to 60 drops / min. Add 0.6-0.8 times of diisopropyl peroxydicarbonate, cool to 63-65°C, continue stirring for 59-61 min, add 30% hydrogen peroxide, glacial acetic acid and chromium dichloride in a mass ratio of 1:5:0.06-1:7:0.08, wherein the mass of hydrogen peroxide is 1.2-1.4 times of the mass of 4-methylphenylacrylic acid, heat to 130-150°C, continue stirring for 70-90 min, and obtain polybenzaldehyde-based ethylene glycol acrylate.
[0015] Furthermore, the mass ratio of silver to copper in the silver-copper catalyst in step (3) is 25:75 to 75:25.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: The highly breathable and wear-resistant medical composite fabric prepared by the present invention comprises a hydrophobic layer and a wear-resistant layer from bottom to top. Firstly, amino carbon nanotubes and polyvinyl iodophenyl acetonitrile are mixed and reacted to obtain carbon nanotube resin. Subsequently, the carbon nanotube resin and polybenzaldehyde-based ethylene glycol acrylate are mixed and reacted to spin and melt-blown to obtain a wear-resistant layer. Then, polyethynylphenylacetic acid butanediol is spun, twisted and braided to obtain a hydrophobic layer. Finally, the hydrophobic layer and the wear-resistant layer are layered from bottom to top, and hydrothermal rolling is performed using sodium hydrosulfide to obtain the highly breathable and wear-resistant medical composite fabric.
[0017] Firstly, part of the aniline on the aminated carbon nanotubes reacts with the iodobenzene on the polyvinyl iodobenzene acetonitrile to uniformly disperse the carbon nanotubes in the carbon nanotube resin, forming a hyperbranched structure containing triphenylamine, thereby enhancing the air permeability of the wear-resistant layer; polybenzaldehyde-based ethylene glycol acrylate quickly enters the cavity of the carbon nanotube resin, and the cyanide group in the polyvinyl iodobenzene acetonitrile is hydrolyzed to form acetic acid, which reacts with the ethanol on the polyethylene glycol acrylate to form a semi-interpenetrating network structure containing ethyl acetate, thereby enhancing the crosslinking density of the wear-resistant layer, thereby enhancing the wear resistance of the wear-resistant layer.
[0018] Secondly, sodium hydrosulfide is hydrolyzed to form sodium hydroxide and hydrogen sulfide. Under the action of sodium hydroxide, the diisobutyl ester on the hydrophobic layer is hydrolyzed. While a large number of pores are formed in the hydrophobic layer, diisobutyl ester and phenylacetic acid are formed. Hydrogen sulfide and diisobutyl ester vaporized at high temperature escape and are adsorbed by the wear-resistant layer. The ethyl acetate on the wear-resistant layer reacts with the phenylacetic acid in the hydrophobic layer to form ethyl acetoacetate. Ethyl acetoacetate reacts with chloroacetyl ketone and hydrogen sulfide in the wear-resistant layer to form thiophene. Thiophene is polymerized to form polythiophene. Then a silver-copper catalyst is introduced to oxidize diisobutyl ester to form Diacetyl reacts with aniline and benzaldehyde on the wear-resistant layer to form pyrrolopyrrole, which forms a heterojunction with the carbon nanotubes in the wear-resistant layer. When light shines on the heterojunction, the pyrrolopyrrole in the wear-resistant layer absorbs photons and generates electron-hole pairs. The electron-hole pairs separate under the action of the built-in potential, and the electrons move toward the pyrrolopyrrole, forming a current loop with the conductive polythiophene, forming a photocurrent to destroy the bacterial cell membrane, change the permeability of the bacteria, and thus kill the bacteria, thereby enhancing the antibacterial properties of the highly breathable and wear-resistant medical composite fabric. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the highly breathable and wear-resistant medical composite fabrics prepared in the following examples as follows: Air permeability: The highly breathable and wear-resistant medical composite fabrics prepared in the embodiment and the comparative example of the same mass were taken and the air permeability was measured according to GB / T5453 to test the air permeability.
[0021] Wear resistance: The wear resistance of the highly breathable and wear-resistant medical composite fabrics prepared in the embodiment and the comparative example of the same mass was measured according to ISO5981 standard.
[0022] Antibacterial performance: The antibacterial rate of the highly breathable and wear-resistant medical composite fabrics prepared in the embodiment and the comparative example of the same mass was tested under an illumination of 200 lx according to the GB / T20944.3 standard method. Example 1
[0023] (1) CNTs and concentrated sulfuric acid were mixed at a mass ratio of 1:210, ultrasonically vibrated at 38 kHz for 25 min, then 68% concentrated nitric acid (557 times the mass of the CNTs) was added, stirred at 1200 r / min for 9 min, heated to 58°C, stirred for 1.5 h, diluted with deionized water (98 times the mass of the CNTs), allowed to stand for 3.5 h, and then vacuum filtered with a microporous filter membrane with a pore size of 220 nm, washed with deionized water until the filtrate pH was 7, then washed twice with anhydrous ethanol, and dried at 55°C. The acidified carbon nanotubes were added to 20 times the mass of ether, ultrasonicated at 38kHz for 25 minutes, 1-(4-amino-2-hydroxyphenyl)-2,2-dichloro-ethanone was added at 0.8 times the mass of the acidified carbon nanotubes, and concentrated sulfuric acid was added at 40 drops / min at 0.6 times the mass of the acidified carbon nanotubes. The temperature was raised to 60°C, and stirring was continued for 1 hour. The mixture was filtered, washed twice with anhydrous ethanol and deionized water, respectively, and dried in an oven at 55°C for 40 minutes to obtain amino carbon nanotubes. (2) Under argon protection, polyvinyl chloride with a molecular weight of 8000 and 4-iodobenzeneacetonitrile were mixed in a mass ratio of 1:1.2, stirred at 300 r / min for 20 min, and then 0.02 times the mass of polyvinyl chloride was added with aluminum chloride, cooled to 0°C at 4°C / min, and stirred at 500 r / min for 7 h to obtain polyvinyl iodobenzeneacetonitrile; (3) Under argon protection, polyvinyl iodobenzene acetonitrile and amino carbon nanotubes were mixed in a mass ratio of 1:0.6, ultrasonically oscillated at 38 kHz for 25 min, and then sodium hydride and copper were added in a mass ratio of 1:0.2, wherein the mass of sodium hydride was 0.4 times the mass of polyvinyl iodobenzene acetonitrile. The temperature was raised to 110°C, and stirred at 300 r / min for 12 h at 10 Pa to obtain carbon nanotube resin; (4) Under argon protection, 4-methylphenylacrylic acid and ethylene glycol were mixed in a mass ratio of 1:0.6, concentrated sulfuric acid (0.6 times the mass of 4-methylphenylacrylic acid) was added at a rate of 40 drops / min, the temperature was raised to 70°C, and the mixture was stirred at 600 r / min for 2 h. Diisopropyl peroxydicarbonate (0.6 times the mass of 4-methylphenylacrylic acid) was added at a rate of 40 drops / min, the temperature was lowered to 63°C, and the stirring was continued for 59 min. Hydrogen peroxide (30% by mass), glacial acetic acid and chromium dichloride (30% by mass) were added in a rate of 1:5:0.06, wherein the mass of hydrogen peroxide was 1.2 times the mass of 4-methylphenylacrylic acid, the temperature was raised to 130°C, and the stirring was continued for 70 min to obtain polybenzaldehyde-based ethylene glycol acrylate. (5) Under argon protection, carbon nanotube resin, polybenzaldehyde-based ethylene glycol acrylate, acetic acid, and deionized water were mixed in a mass ratio of 1:0.7:0.2:0.7, and 80% sulfuric acid with a mass fraction of 0.2 times the mass of the carbon nanotube resin was added at 40 drops / min. The mixture was stirred at 400r / min for 2h, and the mixture was placed in a melt-blowing device with a screen roller speed of 92m / min, a melt-blowing die aperture of 5μm, a die temperature of 221°C, and a hot air pressure of 0.21MPa. The receiving distance was adjusted to 38cm, the extrusion frequency to 1.5Hz, and the hot air temperature to 245°C for melt-blowing. The electret voltage was controlled to 38kV and the electret distance to 2.5cm for electret 0.8min to obtain a 0.8mm thick wear-resistant layer. (6) Under argon protection, 4-ethynylphenylacetic acid and dibutyl alcohol were mixed in a mass ratio of 1:0.5, concentrated sulfuric acid with a mass of 0.6 times that of 4-ethynylphenylacetic acid was added at 40 drops / min, the temperature was raised to 140°C, and the mixture was stirred at 600 r / min for 2 h. Diisopropyl peroxydicarbonate with a mass of 0.6 times that of 4-ethynylphenylacetic acid was added at 40 drops / min, the temperature was lowered to 63°C, and the mixture was stirred for 59 min to obtain polyethynylphenylacetic acid dibutyl alcohol ester; polyethynylphenylacetic acid dibutyl alcohol ester was placed in a spinning box at 140°C, and spun using a screw extruder at a spinning speed of 800 m / min. The mixture was cooled and solidified by side blowing for 25 min at 10°C, a humidity of 60% and a wind speed of 0.9 m / s, and co-twisted and woven to obtain a 0.3 mm thick hydrophobic layer; (7) Lay the hydrophobic layer and the wear-resistant layer from bottom to top, immerse them in deionized water 0.7 times the mass of the hydrophobic layer, roll them twice at a rolling speed of 123 m / min, a roller distance of 1.4 mm and a pressure of 0.25 MPa, add sodium hydrosulfide 0.5 times the mass of the hydrophobic layer, stir at 600 r / min at 60°C and 0.3 MPa for 30 min, add sodium 0.6 times the mass of the hydrophobic layer, heat to 183°C, continue stirring for 3 h, cool to -1°C, add Add 0.54 times the mass of the hydrophobic layer of triethylamine, continue stirring for 51 hours, raise the temperature to 24°C, add 0.02 times the mass of the hydrophobic layer of silver-copper catalyst with a mass ratio of 25:75, continue stirring for 7 hours, then add 0.004 times the mass of the hydrophobic layer of 4-methylbenzenesulfonic acid and 5 times the mass of the hydrophobic layer of acetic acid, raise the temperature to 88°C, continue stirring for 11 hours, remove, wash twice with ethanol and deionized water, put into a 55°C oven for 6 hours, and obtain a highly breathable and wear-resistant medical composite fabric. Example 2
[0024] (1) CNTs and concentrated sulfuric acid were mixed at a mass ratio of 1:220, ultrasonically vibrated at 43 kHz for 30 min, then 68% concentrated nitric acid (56 times the mass of the CNTs) was added, stirred at 1300 r / min for 10 min, heated to 60°C, stirred for 2 h, diluted with deionized water (100 times the mass of the CNTs), allowed to stand for 4 h, and then vacuum filtered with a microporous filter membrane with a pore size of 220 nm, washed with deionized water until the filtrate pH was 7, then washed with anhydrous ethanol for 3 times, and dried in an oven at 60°C. The acidified carbon nanotubes were added to 25 times the mass of ether, ultrasonicated at 43kHz for 30 minutes, 1-(4-amino-2-hydroxyphenyl)-2,2-dichloro-ethanone was added at 0.9 times the mass of the acidified carbon nanotubes, and concentrated sulfuric acid was added at 50 drops / min at 0.7 times the mass of the acidified carbon nanotubes, the temperature was raised to 70°C, stirring was continued for 2 hours, filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried in an oven at 60°C for 50 minutes to obtain amino carbon nanotubes; (2) Under argon protection, polyvinyl chloride with a molecular weight of 9000 and 4-iodobenzeneacetonitrile were mixed in a mass ratio of 1:1.3, stirred at 400 r / min for 25 min, and then 0.04 times the mass of polyvinyl chloride was added with aluminum chloride, cooled to 2°C at 5°C / min, and stirred at 600 r / min for 8 h to obtain polyvinyl iodobenzeneacetonitrile; (3) Under argon protection, polyvinyl iodobenzene acetonitrile and amino carbon nanotubes were mixed in a mass ratio of 1:0.7, ultrasonically oscillated at 43 kHz for 30 min, and then sodium hydride and copper were added in a mass ratio of 1:0.3, wherein the mass of sodium hydride was 0.5 times the mass of polyvinyl iodobenzene acetonitrile. The temperature was raised to 115°C, and stirred at 400 r / min for 12.5 h at 15 Pa to obtain carbon nanotube resin; (4) Under argon protection, 4-methylphenylacrylic acid and ethylene glycol were mixed in a mass ratio of 1:0.7, concentrated sulfuric acid (0.7 times the mass of 4-methylphenylacrylic acid) was added at a rate of 50 drops / min, the temperature was raised to 75°C, and the mixture was stirred at 700 r / min for 3 h. Diisopropyl peroxydicarbonate (0.7 times the mass of 4-methylphenylacrylic acid) was added at a rate of 50 drops / min, the temperature was lowered to 64°C, and the stirring was continued for 60 min. Hydrogen peroxide (30%), glacial acetic acid, and chromium dichloride (mass fraction) were added in a rate of 1:6:0.07, wherein the mass of hydrogen peroxide was 1.3 times the mass of 4-methylphenylacrylic acid, the temperature was raised to 140°C, and the stirring was continued for 80 min to obtain polybenzaldehyde-based ethylene glycol acrylate. (5) Under argon protection, carbon nanotube resin, polybenzaldehyde-based ethylene glycol acrylate, acetic acid, and deionized water were mixed in a mass ratio of 1:0.8:0.3:0.8, and 80% sulfuric acid with a mass fraction of 0.3 times the mass of the carbon nanotube resin was added at 50 drops / min, and stirred at 500r / min for 3h. The mixture was placed in a melt-blowing device with a screen roller speed of 94m / min, a melt-blowing die aperture of 6μm, a die temperature of 223°C, and a hot air pressure of 0.22MPa. The receiving distance was adjusted to 40cm, the extrusion frequency to 2Hz, and the hot air temperature to 250°C for melt-blowing. The electret voltage was controlled to 40kV and the electret distance to 3cm for electret 1min to obtain a 1mm thick wear-resistant layer. (6) Under argon protection, 4-ethynylphenylacetic acid and dibutyl alcohol were mixed in a mass ratio of 1:0.6, concentrated sulfuric acid with a mass of 0.7 times that of 4-ethynylphenylacetic acid was added at a rate of 50 drops / min, the temperature was raised to 145°C, and the mixture was stirred at 700 r / min for 3 h. Diisopropyl peroxydicarbonate with a mass of 0.7 times that of 4-ethynylphenylacetic acid was added at a rate of 50 drops / min, the temperature was lowered to 64°C, and the mixture was stirred for 60 min to obtain polyethynylphenylacetic acid dibutyl alcohol ester; polyethynylphenylacetic acid dibutyl alcohol ester was placed in a spinning box at 150°C, and spun using a screw extruder at a spinning speed of 900 m / min. The mixture was cooled and solidified by side blowing for 30 min at a rate of 15°C, a humidity of 70%, and a wind speed of 1.1 m / s. The mixture was co-twisted and woven to obtain a 0.4 mm thick hydrophobic layer; (7) Lay the hydrophobic layer and the wear-resistant layer from bottom to top, immerse them in deionized water 0.75 times the mass of the hydrophobic layer, roll them 3 times at a rolling speed of 191 m / min, a roller distance of 2.1 mm, and a pressure of 0.3 MPa, add sodium hydrosulfide 0.6 times the mass of the hydrophobic layer, stir at 700 r / min at 70°C and 0.4 MPa for 35 min, add sodium 0.7 times the mass of the hydrophobic layer, heat to 184°C, continue stirring for 4 h, cool to 0°C, add Add 0.55 times the mass of the hydrophobic layer of triethylamine, continue stirring for 52 hours, raise the temperature to 25°C, add 0.03 times the mass of the hydrophobic layer of silver-copper catalyst with a mass ratio of 50:50, continue stirring for 8 hours, then add 0.005 times the mass of the hydrophobic layer of 4-methylbenzenesulfonic acid and 6 times the mass of the hydrophobic layer of acetic acid, raise the temperature to 90°C, continue stirring for 12 hours, remove, wash with ethanol and deionized water 3 times, put into a 60°C oven for 7 hours, and obtain a highly breathable and wear-resistant medical composite fabric. Example 3
[0025] (1) CNTs and concentrated sulfuric acid were mixed at a mass ratio of 1:230, ultrasonically vibrated at 47 kHz for 35 min, then 68% concentrated nitric acid (57 times the mass of the CNTs) was added, stirred at 1400 r / min for 11 min, heated to 62°C, stirred for 2.5 h, diluted with deionized water (102 times the mass of the CNTs), allowed to stand for 4.5 h, and then vacuum filtered with a microporous filter membrane with a pore size of 220 nm, washed with deionized water until the filtrate pH was 7, then washed with anhydrous ethanol 4 times, and placed at 65°C. The acidified carbon nanotubes were dried in an oven for 60 minutes to obtain acidified carbon nanotubes; the acidified carbon nanotubes were added to 30 times the mass of ether, ultrasonicated at 47kHz for 35 minutes, 1-(4-amino-2-hydroxyphenyl)-2,2-dichloro-ethanone was added at 1 times the mass of the acidified carbon nanotubes, and concentrated sulfuric acid was added at 60 drops / min at 0.8 times the mass of the acidified carbon nanotubes, the temperature was raised to 80°C, stirring was continued for 3 hours, filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried in an oven at 65°C for 60 minutes to obtain amino carbon nanotubes; (2) Under argon protection, polyvinyl chloride with a molecular weight of 10,000 and 4-iodobenzeneacetonitrile were mixed in a mass ratio of 1:1.4, stirred at 500 r / min for 30 min, and then 0.06 times the mass of polyvinyl chloride was added with aluminum chloride, cooled to 4°C at 6°C / min, and stirred at 700 r / min for 9 h to obtain polyvinyl iodobenzeneacetonitrile; (3) Under argon protection, polyvinyl iodobenzene acetonitrile and amino carbon nanotubes were mixed in a mass ratio of 1:0.8, ultrasonically oscillated at 47 kHz for 35 min, and then sodium hydride and copper were added in a mass ratio of 1:0.4, wherein the mass of sodium hydride was 0.6 times the mass of polyvinyl iodobenzene acetonitrile. The mixture was heated to 120°C and stirred at 500 r / min for 13 h at 20 Pa to obtain carbon nanotube resin. (4) Under argon protection, 4-methylphenylacrylic acid and ethylene glycol were mixed in a mass ratio of 1:0.8, concentrated sulfuric acid (0.8 times the mass of 4-methylphenylacrylic acid) was added at a rate of 60 drops / min, the temperature was raised to 80°C, and the mixture was stirred at 800 r / min for 4 h. Diisopropyl peroxydicarbonate (0.8 times the mass of 4-methylphenylacrylic acid) was added at a rate of 60 drops / min, the temperature was lowered to 65°C, and the stirring was continued for 61 min. Hydrogen peroxide (30%), glacial acetic acid, and chromium dichloride (mass fraction) were added in a rate of 1:7:0.08, wherein the mass of hydrogen peroxide was 1.4 times the mass of 4-methylphenylacrylic acid, the temperature was raised to 150°C, and the stirring was continued for 90 min to obtain polybenzaldehyde-based ethylene glycol acrylate. (5) Under argon protection, carbon nanotube resin, polybenzaldehyde-based ethylene glycol acrylate, acetic acid, and deionized water were mixed in a mass ratio of 1:0.9:0.4:0.9, and 80% sulfuric acid with a mass fraction of 0.4 times the mass of the carbon nanotube resin was added at 60 drops / min. The mixture was stirred at 600r / min for 4h, and the mixture was placed in a melt-blowing device with a screen roller speed of 96m / min, a melt-blowing die aperture of 7μm, a die temperature of 225°C, and a hot air pressure of 0.23MPa. The receiving distance was adjusted to 42cm, the extrusion frequency to 2.5Hz, and the hot air temperature to 255°C for melt-blowing. The electret voltage was controlled to 42kV, and the electret distance was controlled to 3.5cm for electret 1.2min to obtain a 1.2mm thick wear-resistant layer. (6) Under argon protection, 4-ethynylphenylacetic acid and dibutyl alcohol were mixed in a mass ratio of 1:0.7, concentrated sulfuric acid with a mass of 0.8 times that of 4-ethynylphenylacetic acid was added at a rate of 60 drops / min, the temperature was raised to 150°C, and the mixture was stirred at 800 r / min for 4 h. Diisopropyl peroxydicarbonate with a mass of 0.8 times that of 4-ethynylphenylacetic acid was added at a rate of 60 drops / min, the temperature was lowered to 65°C, and the mixture was stirred for 61 min to obtain polyethynylphenylacetic acid dibutyl alcohol ester; polyethynylphenylacetic acid dibutyl alcohol ester was placed in a spinning box at 160°C, and spun using a screw extruder at a spinning speed of 1000 m / min. The mixture was cooled and solidified by side blowing for 35 min at a temperature of 20°C, a humidity of 80%, and a wind speed of 1.3 m / s. The mixture was co-twisted and woven to obtain a 0.5 mm thick hydrophobic layer; (7) Lay the hydrophobic layer and the wear-resistant layer from bottom to top, immerse them in deionized water 0.8 times the mass of the hydrophobic layer, roll them 3 times at a rolling speed of 260 m / min, a roller distance of 2.9 mm and a pressure of 0.35 MPa, add sodium hydrosulfide 0.7 times the mass of the hydrophobic layer, stir at 800 r / min at 80°C and 0.5 MPa for 40 min, add sodium 0.8 times the mass of the hydrophobic layer, heat to 185°C, continue stirring for 5 h, cool to 1°C, and add Add 0.56 times the mass of the hydrophobic layer of triethylamine, continue stirring for 53 hours, raise the temperature to 26°C, add 0.04 times the mass of the hydrophobic layer of silver-copper catalyst with a mass ratio of 75:25, continue stirring for 9 hours, then add 0.006 times the mass of the hydrophobic layer of 4-methylbenzenesulfonic acid and 7 times the mass of the hydrophobic layer of acetic acid, raise the temperature to 92°C, continue stirring for 13 hours, remove from the water, wash with ethanol and deionized water 4 times, put into a 65°C oven for 8 hours, and obtain a highly breathable and wear-resistant medical composite fabric.
[0026] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that no amino carbon nanotubes are prepared, and carbon nanotubes and polyvinyl iodophenyl acetonitrile are used to prepare carbon nanotube resin. The remaining preparation steps are the same as those in Example 2.
[0027] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that polyvinyl iodophenyl acetonitrile is not prepared, and only amino carbon nanotubes and polybenzaldehyde ethylene glycol acrylate are used to prepare the wear-resistant layer. The remaining preparation steps are the same as those of Example 2.
[0028] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that only carbon nanotube resin is used to prepare the wear-resistant layer. The remaining preparation steps are the same as those of Example 2.
[0029] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that only polypropylene is used to prepare the hydrophobic layer. The remaining preparation steps are the same as those of Example 2.
[0030] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that the hydrophobic layer and the wear-resistant layer are only layered and rolled from bottom to top to prepare the highly breathable and wear-resistant medical composite fabric. The remaining preparation steps are the same as those in Example 2.
[0031] Effect example Table 1 below shows the analysis results of the air permeability, wear resistance and antibacterial properties of the highly air-permeable and wear-resistant medical composite fabrics prepared by Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0032] Table 1
[0033] From Table 1, it can be found that the highly breathable and wear-resistant medical composite fabrics prepared in Examples 1, 2, and 3 have good air permeability, wear resistance, and antibacterial properties; from the comparison of the experimental data of Examples 1, 2, and 3 and Comparative Examples 1 and 5, it can be found that the wear-resistant layer is prepared by using the carbon nanotube resin prepared by amino carbon nanotubes, and a hyperbranched structure can be formed, and the highly breathable and wear-resistant medical composite fabric is subsequently prepared by hydrothermal rolling with sodium hydrosulfide, which can form polythiophene, and the highly breathable and wear-resistant medical composite fabric has good air permeability and antibacterial properties; from the experimental data of Examples 1, 2, 3 and Comparative Examples 2 and 5, it can be found that the wear-resistant layer is prepared by using the carbon nanotube resin prepared by polyvinyl iodophenyl acetonitrile, and a hyperbranched structure and a semi-interpenetrating network structure containing ethyl acetate can be formed, and the highly breathable and wear-resistant medical composite fabric is subsequently prepared by hydrothermal rolling with sodium hydrosulfide, which can form polythiophene. The highly breathable and wear-resistant medical composite fabric has good air permeability, wear resistance and antibacterial properties; from the experimental data of Examples 1, 2, 3 and Comparative Examples 3 and 5, it can be found that the wear-resistant layer is prepared by using polybenzaldehyde-based ethylene glycol acrylate, and a semi-interpenetrating network structure containing ethyl acetate can be formed, and the highly breathable and wear-resistant medical composite fabric is subsequently prepared by hydrothermal rolling using sodium hydrosulfide, which can form polythiophene and pyrrolopyrrole, and the wear resistance and antibacterial properties of the prepared highly breathable and wear-resistant medical composite fabric are good; from the experimental data of Examples 1, 2, 3 and Comparative Examples 4 and 5, it can be found that the hydrophobic layer is prepared by using polyethynylphenylacetic acid butanediol ester, and the highly breathable and wear-resistant medical composite fabric is subsequently prepared by hydrothermal rolling using sodium hydrosulfide, which can form polythiophene and pyrrolopyrrole, and the antibacterial properties of the prepared highly breathable and wear-resistant medical composite fabric are good.
[0034] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A highly breathable and wear-resistant medical composite fabric, characterized in that: The highly breathable and wear-resistant medical composite fabric is obtained by laminating a hydrophobic layer and a wear-resistant layer from bottom to top and performing hydrothermal roller pressing using sodium hydrosulfide.
2. The highly breathable and wear-resistant medical composite fabric according to claim 1, characterized in that: The wear-resistant layer is prepared by mixing carbon nanotube resin and polybenzaldehyde-based ethylene glycol acrylate through reaction spinning and melt-blowing.
3. The highly breathable and wear-resistant medical composite fabric according to claim 2, characterized in that: The carbon nanotube resin is prepared by mixing and reacting amination carbon nanotubes and polyvinyl iodobenzene acetonitrile; the amination carbon nanotubes are prepared by mixing and reacting 1-(4-amino-2-hydroxyphenyl)-2,2-dichloro-ethanone and acidified carbon nanotubes.
4. The highly breathable and wear-resistant medical composite fabric according to claim 1, characterized in that: The hydrophobic layer is obtained by spinning and twisting polyethynylphenylacetic acid butylene glycol ester.
5. A method for preparing a highly breathable and wear-resistant medical composite fabric, characterized in that: The preparation method of the highly breathable and wear-resistant medical composite fabric is as follows: (1) Under argon protection, carbon nanotube resin, polybenzaldehyde-based ethylene glycol acrylate, acetic acid, and deionized water were mixed in a mass ratio of 1:0.7:0.2:0.7 to 1:0.9:0.4:0.9, and 80% sulfuric acid with a mass fraction of 0.2 to 0.4 times the mass of the carbon nanotube resin was added at 40 to 60 drops / min, stirred at 400 to 600 r / min for 2 to 4 hours, and placed in a condensation drum with a rotation speed of 92 to 96 m / min and a melt-blown die. In a melt-blowing device with a head aperture of 5 to 7 μm, a die temperature of 221 to 225° C., and a hot air pressure of 0.21 to 0.23 MPa, the receiving distance is adjusted to 38 to 42 cm, the extrusion frequency is adjusted to 1.5 to 2.5 Hz, and the hot air temperature is adjusted to 245 to 255° C. for melt-blowing, and then the electret voltage is controlled to 38 to 42 kV, and the electret distance is 2.5 to 3.5 cm for electret 0.8 to 1.2 min to obtain a 0.8 to 1.2 mm thick wear-resistant layer; (2) Under argon protection, 4-ethynylphenylacetic acid and butanediol were mixed at a mass ratio of 1:0.5 to 1:0.7, concentrated sulfuric acid in an amount of 0.6 to 0.8 times the mass of 4-ethynylphenylacetic acid was added dropwise at a rate of 40 to 60 drops / min, the temperature was raised to 140 to 150°C, and the mixture was stirred at a rate of 600 to 800 r / min for 2 to 4 hours. Diisopropyl peroxydicarbonate in an amount of 0.6 to 0.8 times the mass of 4-ethynylphenylacetic acid was added dropwise at a rate of 40 to 60 drops / min, the temperature was lowered to 63 to 65°C, and the mixture was continued. Stirring for 59 to 61 minutes to obtain polyethynylphenylacetic acid butylene glycol ester; placing the polyethynylphenylacetic acid butylene glycol ester in a spinning box at 140 to 160° C., spinning with a screw extruder at a spinning speed of 800 to 1000 m / min, cooling and curing with side blowing for 25 to 35 minutes at 10 to 20° C., a humidity of 60 to 80% and a wind speed of 0.9 to 1.3 m / s, co-twisting and braiding to obtain a hydrophobic layer with a thickness of 0.3 to 0.5 mm; (3) Lay the hydrophobic layer and the wear-resistant layer from bottom to top, immerse them in deionized water 0.7 to 0.8 times the mass of the hydrophobic layer, roll them 2 to 3 times at a rolling speed of 123 to 260 m / min, a roller distance of 1.4 to 2.9 mm, and a pressure of 0.25 to 0.35 MPa, add sodium hydrosulfide 0.5 to 0.7 times the mass of the hydrophobic layer, stir at 600 to 800 r / min at 60 to 80 ° C and 0.3 to 0.5 MPa for 30 to 40 minutes, add sodium 0.6 to 0.8 times the mass of the hydrophobic layer, heat to 183 to 185 ° C, and continue stirring for 3 to 5 hours , cool to -1~1°C, add triethylamine (0.54~0.56 times the mass of the hydrophobic layer), continue stirring for 51~53h, heat to 24~26°C, add silver-copper catalyst (0.02~0.04 times the mass of the hydrophobic layer), continue stirring for 7~9h, then add 4-methylbenzenesulfonic acid (0.004~0.006 times the mass of the hydrophobic layer) and acetic acid (5~7 times the mass of the hydrophobic layer), heat to 88~92°C, continue stirring for 11~13h, remove, wash with ethanol and deionized water 2~4 times, put into 55~65°C oven for 6~8h, and obtain highly breathable and wear-resistant medical composite fabric.
6. The method for preparing a highly breathable and wear-resistant medical composite fabric according to claim 5, characterized in that: The preparation method of the carbon nanotube resin in step (1) is as follows: under argon protection, polyvinyl iodobenzene acetonitrile and amino carbon nanotubes are mixed in a mass ratio of 1:0.6 to 1:0.8, ultrasonically oscillated at 38 to 47 kHz for 25 to 35 minutes, and then sodium hydride and copper are added in a mass ratio of 1:0.2 to 1:0.4, wherein the mass of sodium hydride is 0.4 to 0.6 times the mass of polyvinyl iodobenzene acetonitrile, heated to 110 to 120° C., and stirred at 300 to 500 r / min for 12 to 13 hours at 10 to 20 Pa to obtain the carbon nanotube resin.
7. The method for preparing a highly breathable and wear-resistant medical composite fabric according to claim 6, characterized in that: The preparation method of the polyvinyl iodobenzene acetonitrile is as follows: under argon protection conditions, polyvinyl chloride with a molecular weight of 8000-10000 and 4-iodobenzene acetonitrile are mixed in a mass ratio of 1:1.2-1:1.4, stirred at 300-500 r / min for 20-30 min, then aluminum chloride with a mass of 0.02-0.06 times of the mass of the polyvinyl chloride is added, the temperature is reduced to 0-4°C at 4-6°C / min, and stirred at 500-700 r / min for 7-9h to obtain polyvinyl iodobenzene acetonitrile.
8. The method for preparing a highly breathable and wear-resistant medical composite fabric according to claim 5, characterized in that: The preparation method of the amino carbon nanotubes in step (1) is as follows: carbon nanotubes and concentrated sulfuric acid are mixed in a mass ratio of 1:210 to 1:230, ultrasonically oscillated at 38 to 47 kHz for 25 to 35 minutes, then concentrated nitric acid with a mass fraction of 68% of 55 to 57 times the mass of the carbon nanotubes is added, stirred at 1200 to 1400 r / min for 9 to 11 minutes, heated to 58 to 62° C., stirred for 1.5 to 2.5 hours, and deionized water with a mass of 98 to 102 times the mass of the carbon nanotubes is added for dilution, allowed to stand for 3.5 to 4.5 hours, and then vacuum filtered with a microporous filter membrane with a pore size of 220 nm, washed with deionized water until the filtrate pH was 7, and then washed with anhydrous ethanol for 2 hours. The method comprises the following steps: adding the acidified carbon nanotubes to 20 to 30 times of the mass of ether, ultrasonicating at 38 to 47 kHz for 25 to 35 minutes, adding 1-(4-amino-2-hydroxyphenyl)-2,2-dichloro-ethanone in an amount of 0.8 to 1 times of the mass of the acidified carbon nanotubes, adding concentrated sulfuric acid in an amount of 0.6 to 0.8 times of the mass of the acidified carbon nanotubes at a rate of 40 to 60 drops / min, heating to 60 to 80°C, stirring continuously for 1 to 3 hours, filtering, washing with anhydrous ethanol and deionized water for 2 to 4 times respectively, and drying in an oven at 55 to 65°C for 40 to 60 minutes to obtain amino-treated carbon nanotubes.
9. The method for preparing a highly breathable and wear-resistant medical composite fabric according to claim 5, characterized in that: The preparation method of the polybenzaldehyde-based ethylene glycol acrylate in step (1) is as follows: under argon protection, 4-methylphenylacrylic acid and ethylene glycol are mixed in a mass ratio of 1:0.6 to 1:0.8, concentrated sulfuric acid with a mass of 0.6 to 0.8 times that of 4-methylphenylacrylic acid is added at a rate of 40 to 60 drops / min, the temperature is raised to 70 to 80° C., stirred at 600 to 800 r / min for 2 to 4 hours, and 4-methylphenylacrylic acid with a mass of 0.03 to 0.07 is added at a rate of 40 to 60 drops / min. .6 to 0.8 times of diisopropyl peroxydicarbonate, cool to 63 to 65°C, continue stirring for 59 to 61 minutes, add 30% hydrogen peroxide, glacial acetic acid and chromium dichloride in a mass ratio of 1:5:0.06 to 1:7:0.08, wherein the mass of hydrogen peroxide is 1.2 to 1.4 times of the mass of 4-methylphenylacrylic acid, heat to 130 to 150°C, continue stirring for 70 to 90 minutes to obtain polybenzaldehyde-based ethylene glycol acrylate.
10. The method for preparing a highly breathable and wear-resistant medical composite fabric according to claim 5, characterized in that: The mass ratio of silver to copper in the silver-copper catalyst of step (3) is 25:75 to 75:25.
Citation Information
Patent Citations
Preparation method of polymer-modified carbon-nanotube-reinforced mixed resin composite material
CN104945850A
Rubber and plastic foaming aid and preparation method thereof
CN113512231A
High-strength anti-tearing fabric and preparation method thereof
CN115821586A
Dustproof antistatic acoustic screen cloth and preparation method thereof
CN117449033A
Anti-electron-radiation garment fabric and preparation method therefor
WO2023123376A1